Design of pinned and rigid bolted connections using BS 5950:2000 and Eurocode 3 - Xie, Yunshen. (2011)
In structural design, engineers typically follow a set of standards or codes. Not all countries published their own standards or codes, those that do not typically adopt those recognized and readily available ones. In Singapore, the British Standards were adopted for most of the civil and structural engineering works.